Standard specification for lead-coated copper sheet and strip for building construction
This specification establishes the requirements for leadcoated copper sheet and strip in flat lengths (or in coils) in ounce-weight thicknesses for roofing, flashing, gutters, downspouts, and for the general sheet metalwork in building construction. The lead coating is applied by hot dipping. Materials made to this specification are not intended for electrical applications.